Administration of turmeric kombucha ameliorates lipopolysaccharide-induced sepsis by attenuating inflammation and modulating gut microbiota - Su, Jingqian; Tan, Qingqing; Wu, Shun; Zhou, Fen; Xu, Chen; Zhao, Heng; Lin, Congfan; Deng, Xiaohui; Xie, Lian; Lin, Xinrui; Ye, Hui; Yang, Minhe (Frontiers in Microbiology, 2024)
Our research team previously reported the immunomodulatory effects of kombucha fermentation liquid. This study investigated the protective effects of turmeric kombucha (TK) against lipopolysaccharide (LPS)-induced sepsis and its impact on the intestinal microbiota of mice. A turmeric culture medium without kombucha served as the control (TW). Non-targeted metabolomics analysis was employed to analyze the compositional differences between TK and TW. Qualitative analysis identified 590 unique metabolites that distinguished TK from TW. TK improved survival from 40 to 90%, enhanced thermoregulation, and reduced pro-inflammatory factor expression and inflammatory cell infiltration in the lung tissue, suppressing the NF-κB signaling pathway. TK also altered the microbiome, promoting Allobaculum growth. Our findings shed light on the protective effects and underlying mechanisms of TK in mitigating LPS-induced sepsis, highlighting TK as a promising anti-inflammatory agent and revealing new functions of kombucha prepared through traditional fermentation methods.